Integration of photovoltaics and battery system for a hotel building in Desaru - Chua, Ming Jie, 1991-, author; Lau, Kwan Yiew, 1984-, supervisor; Fakulti Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Kejuruteraan (Elektrik Kuasa)) - Universiti Teknologi Malaysia, 2019